Deliberation level of constitutional debates in Georgian Parliament - Napetvaridze Vladimeri (Sciendo, 2020)
In the given paper a discourse quality index (DQI) tool, rooted to criteria elaborated by Jurgen Habermas’s in his discourse ethics, will be modified and used to assess the deliberation level of the 1995 Georgian Parliament. The methodology will accurately represent important principles of deliberation. Due to its focus on observable behavior and its detailed coding instructions, a discourse quality index can be a reliable measurement of the quality of political debates. The DQI for a parliamentary debate in the example of the 1995 parliament of Georgia will be illustrated in the given article. The parliamentarian debates concerning the adoption of the 1995 constitution of Georgia, according to its importance, will be taken as the specific case to be analysed. In the framework of the research, scholars will study and analyse over 200 pages of stenographic recordings of the parliamentary debates connected to the mentioned topic. The DQI score will be evaluated based on the analyses of the stenographic records.